Pengaruh Kehadiran Gulma terhadap Jumlah Populasi Hama Utama Kubis pada Pertanaman Kubis - KETUT AYU YULIADHI; TRISNA AGUNG PHABIOLA; MADE SRITAMIN (Agrotrop : Journal on Agriculture Science, 2013)
The Influence of The Presence of Weeds on The Population Number of main Pest of Cabbage on The Cabbage Croppings The aim of the research was to find out the development of population number of Plutella xylostella and Crocidolomia pavonana in the precence and the absence of weeds on the cabbage croppings. The results showed that there were 23 species of weeds in association with plant cabbage, which was made up of 7 species of grasses, 3 species of weeds from Cyperaceae family, and 13 species of broadleaved weeds. Main pests of cabbage on cabbage croppings (Plutella xylostella and Crocidolomia pavonana) was found more on cabbage plants in the absence of weeds compared than that of the presence of weeds.